Strain-induced structural evolution of interphase interfaces in CuZr-based metallic-glass composite reinforced by B2 crystalline phase. (1st June 2023) - Zhang, Lei; Su, Shuang; Fu, Wujing; Sun, Jianfei; Ning, Zhiliang; Ngan, Alfonso H.W.; Huang, Yongjiang
Abstract: The structural evolution of CuZr-based metallic glass composite (MGC) near the crystalline/matrix interface is studied by in situ transmission electron microscope (TEM) tensile straining and molecular dynamics (MD) simulation. The crystalline phase is found to undergo plastic deformation before the amorphous phase, via recoverable martensite transformation, dislocation accumulation at the interface and local amorphization between grains. Fracture does not occur along the interphase interface, but within the crystalline phase at about half a micron from the interface and parallel to it, indicating a high strength of the interface and an elevated work hardening rate of the crystalline phase just next to the interface. MD simulations show that the amorphous phase is marginally metastable with respect to the stable B2 phase, while B19′ martensitic phase is metastable with a higher energy, thus explaining the easy mutual transformation between B2 and amorphous phase, and the rarer transformation product of B19' phase from B2 on straining. Graphical abstract: Image 1